MANAGEMENT OF EMERGENCY MEASURES PROJECT OF ALGIERS’S KASBAH - Madina Foukroun; Said Madani (International Journal of Innovative Technologies in Social Science, 2024)
Management strategies for the conservation and safeguarding of cultural heritage in general, and urban heritage in particular, have evolved greatly over the past two decades. The relationship between heritage and development is now omnipresent in the policies of construction or reconstruction of territories, where the major challenges lie in their enhancement. Algeria does not have a great deal of experience in the management and administration of heritage safeguarding and enhancement projects, whether urban or architectural, as evidenced by the significant number of projects that remain unfinished or incomplete due to a lack of efficiency. Within the framework of the Permanent Plan for the Safeguarding and Enhancement of the Protected Historic District (PPSMVSS) for the protected historic city of Algiers, emergency projects have been launched to slow down or even stop the deterioration of this heritage site. The objective of this study is to understand the process of formalizing and managing projects in protected historic districts, as well as the interactions between the different stakeholders involved.The methodology used combines on-site surveys, interviews, and questionnaires with the various stakeholders. It refers to the conceptual model of project success factors developed by Pinto and Slevin, in order to evaluate these operations, which have not led to theexpected results.